2012
DOI: 10.1108/17471111211272110
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility, ethics, and corporate governance

Luu Trong Tuan

Abstract: Purpose -This inquiry into companies listed on the Ho Chi Minh City Stock Exchange (HOSE) in Vietnam seeks to discern whether such constructs as corporate social responsibility (CSR) and ethics act as antecedents for corporate governance.Design/methodology/approach -Three hundred and seventeen responses returned from self-administered structured questionnaires relayed to 1,173 middle level managers were analyzed via ANOVAs and structural equation modeling (SEM).Findings -From the results an interplay emerged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 74 publications
2
18
0
1
Order By: Relevance
“…The further research studies are also suggested to apply behavioral finance to explore the behavioral factors of institutional investors at the Stock Exchanges of Vietnam. Ethics should also be included into behavioral factors of institutional investors (Luu, 2012b;Luu, 2012d), especially those in industries in which ethics of stakeholders play a crucial role such as healthcare services (Luu, 2012e;Luu, 2012f;Luu, 2012g). The impact of corporate governance (Luu, 2011;Luu, 2012d;Luu, 2013b;Luu, 2013e) and corporate social responsibility (Luu, 2012d;Luu, 2012g;Luu, 2013a;Luu, 2013c) on behavioral factors of institutional investors can attract researchers as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The further research studies are also suggested to apply behavioral finance to explore the behavioral factors of institutional investors at the Stock Exchanges of Vietnam. Ethics should also be included into behavioral factors of institutional investors (Luu, 2012b;Luu, 2012d), especially those in industries in which ethics of stakeholders play a crucial role such as healthcare services (Luu, 2012e;Luu, 2012f;Luu, 2012g). The impact of corporate governance (Luu, 2011;Luu, 2012d;Luu, 2013b;Luu, 2013e) and corporate social responsibility (Luu, 2012d;Luu, 2012g;Luu, 2013a;Luu, 2013c) on behavioral factors of institutional investors can attract researchers as well.…”
Section: Resultsmentioning
confidence: 99%
“…Ethics should also be included into behavioral factors of institutional investors (Luu, 2012b;Luu, 2012d), especially those in industries in which ethics of stakeholders play a crucial role such as healthcare services (Luu, 2012e;Luu, 2012f;Luu, 2012g). The impact of corporate governance (Luu, 2011;Luu, 2012d;Luu, 2013b;Luu, 2013e) and corporate social responsibility (Luu, 2012d;Luu, 2012g;Luu, 2013a;Luu, 2013c) on behavioral factors of institutional investors can attract researchers as well. The relationship between behavioral factors of institutional investors and marketing effectiveness and brand performance can be another interesting research avenue (Luu, 2012a;Luu, 2012g;Luu, 2013f;Luu, 2012i).…”
Section: Resultsmentioning
confidence: 99%
“…Somers (2001) claims that EL is more related to firm's effectiveness. Although Tuan (2012) and Aslan and Sendogdu (2012) analyze the influence of EL on FP, the magnitude of the influence is still a decisive discussion (Du, Swaen, Lindgreen, & Sen, 2013;Mostovicz et al, 2009). Waddock and Bodwell (2007) considers CSR as "the wide array of strategies and practices" affected by numerous variables, for example, competitors, country of origin, financial position, firm size, management support, and media, social, and regulatory pressure (Maccarrone, 2009;Rai & Bansal, 2015).…”
Section: Literature Review On El Csr and Fpmentioning
confidence: 99%
“…The overwhelming predominance of business literature in the CSR field also points to the value‐added notion of CSR—that doing good is also good for business (“the business case for CSR”). However the origins of CSR in Western (see Carroll, ; Gjølberg, ; Moura‐Leite & Padgett, ) and specifically American (Marens, Fleming, Roberts, & Garsten, ) business and societal culture and the subsequent examination of different cultural lens on the role of business in society (see,e.g., Srisuphaolarn, ; Trong Tuan, ) has largely diverted attention from better understanding and expectations of CSR from the perspective of communities in non‐Western societies. In short, communities in developing/impoverished/remote areas typically perceive this corporate responsibility differently.…”
Section: Introductionmentioning
confidence: 99%